1994
DOI: 10.2307/1592131
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Spirochetosis in Commercial Laying Hens

Abstract: Cecal spirochetosis in chickens has been associated with enteric disease and reduced egg production in the United States and Europe. This report describes spirochete overgrowth of cecal mucosa in chickens from a flock of 100,000 commercial layers experiencing diarrhea and a 5% drop in egg production. Spirochetes were demonstrated in the ceca by darkfield and light microscopy. Apical surfaces of cecal enterocytes were covered by a dense layer of spirochetes aligned parallel to each other and perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 10 publications
4
46
0
1
Order By: Relevance
“…In a commercial situation, this loss would have an extremely serious economic impact. That such losses can occur in practice was seen in Iowa, where a layer flock (100 000 birds) infected with a spirochaete, which was later identified as B. pilosicoli (McLaren et al, 1997), was shown to have an overall 5% reduction in egg production (Trampel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a commercial situation, this loss would have an extremely serious economic impact. That such losses can occur in practice was seen in Iowa, where a layer flock (100 000 birds) infected with a spirochaete, which was later identified as B. pilosicoli (McLaren et al, 1997), was shown to have an overall 5% reduction in egg production (Trampel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…To date, colonization of layer and broiler breeder birds with intestinal spirochaetes has been recorded in continental Europe, the UK, the US and Australia (Davelaar et al, 1986;Griffiths et al, 1987;Dwars et al, 1989;Swayne et al, 1992Swayne et al, , 1995Trampel et al, 1994;McLaren et al, 1996;Stephens & Hampson, 1999). Colonization tends to be chronic in adult birds in infected flocks (Dwars et al, 1990), and has been associated with a variety of symptoms including diarrhoea, increased faecal fat content, faecal staining of eggshells, delayed onset of egg laying, reduced egg weights, reduced growth rates, increased feed consumption and poor digestion of feed (Davelaar et al, 1986;Griffiths et al, 1987;Dwars et al, 1990;Swayne et al, 1992;Dwars et al, 1992aDwars et al, , 1993Trampel et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported examples of problems include pasty vents, wet litter, faecal staining of eggshells, increased fat content of faeces, delayed onset of egg laying, reduced egg production, increased mortalities, and a reduced feed conversion ratio ( Devalaar et al, 1986, Griffiths et al, 1987, Dwars et al, 1989, Swayne et al, 1992, Swayne et al, 1995, Trampel et al, 1994, Hampson and McLaren, 1999, Stephens and Hampson, 2001, Burch et al, 2006and Bano et al, 2008. Broiler flocks derived from infected breeders may show poor feed conversion ratios, a high number of weak chicks, slow growth, and poor feed digestion ( Dwars et al, 1993 andSmith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%